BODIPY–BODIPY dyad: assessing the potential as a viscometer for molecular and ionic liquids1. Issue 25 (21st March 2015) - Kimball, Joseph D.; Raut, Sangram; Jameson, Laramie P.; Smith, Nicholas W.; Gryczynski, Zygmunt; Dzyuba, Sergei V.
<x xml:space="preserve">Abstract</x> The fluorescent lifetimes of the BODIPY–BODIPY dyad appear to correlate with the viscosity of the media, thus making this rotor a suitable small molecule viscometer.